Perilaku Pencarian Informasi Layanan Koleksi Perpustakaan FMIPA Universitas Padjadjaran di Era Digital - Muchtarom, Keysha Husna; Wulandari, Eko Retno (Pustabiblia: Journal of Library and Information Science, 2023)
The college library is one of the collection services provided by the college to obtain information. In conducting information search, there are several information search behaviors. This study examines student information seeking behavior in the collection service of the Padjadjaran University FMIPA Library in the digital era. Information seeking behavior has a very close relationship with information seeking, because then information can be obtained. The purpose of this study was to determine the information seeking behavior of the Unpad FMIPA library collection service through six stages and to determine the relationship between information seeking and information seeking behavior. The research method is qualitative with observation and interviews. This research method was conducted on three Unpad FMIPA students and one Unpad FMIPA librarian. The model used in this study consists of six stages, namely start- ing, chaining, browsing, differentiating, monitoring, and extracting. The result of the research is that students who need information have carried out the six stages well, namely students understand the information needed before starting a search, and are able to identify reference sources in searching for information, students use search information tools and their support- ers. the device with the help of lib.unpad.ac.id, can determine the forms and sources of relevant information that can be used, as well as identify search keywords, and make observations on information relating to their needs. And the last stage students choose information according to their needs and which are considered important. After going through the stages of searching for student information effectively, quickly, and precisely in finding the sources of information needed, especially gathering information at FMIPA Unpad.